Recent advances in technologies for vitamin A protection in foods. - Loveday, SM; Singh, Harjinder (Elsevier, 2008)
Vitamin A deficiency affects many children in the developing world, and is preventable via food or pharmaceutical supplementation. The main technical barrier to the fortification of food with vitamin A is its susceptibility to oxidation and isomerization, which result in loss of nutritional efficacy. This review discusses recent technological avenues for stabilizing vitamin A in foods.
Keywords: Vitamin A; Retinoids; Encapsulation; Nutrition; Neutraceutical; Food fortification; Oxidation; Isomerization; Nanotechnology; Fields of Research::290000 Engineering and Technology::290100 Industrial Biotechnology and Food Sciences::290102 Food engineering